2020
DOI: 10.1016/j.omtn.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Long Non-coding RNA to Therapeutically Regulate Gene Expression in Cancer

Abstract: Long-chain non-coding RNAs (lncRNAs) are RNA molecules with a length greater than 200 nt and no function of encoding proteins. lncRNAs play a precise regulatory function at different levels of transcription and post-transcription, and they interact with various regulatory factors to regulate gene expression, and then participate in cell growth, differentiation, apoptosis, and other life processes. In recent years, studies have shown that the abnormal expression of lncRNAs is closely related to the occurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 135 publications
0
50
0
Order By: Relevance
“…A number of lncRNAs have been identified as potential predictive and prognostic biomarkers including SChLAP1, UCA1 and PCAT14 ( Mehra et al, 2016 ; Fotouhi Ghiam et al, 2017 ; White et al, 2017 ). Further work is exploring lncRNAs as therapeutic targets in PCa using small interfering RNAs (siRNAs), antisense oligonucleotides (ASOs) and small molecule inhibitors ( Fu et al, 2020 ). Therefore, there is significant interest in the role ncRNAs may play in the future management of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…A number of lncRNAs have been identified as potential predictive and prognostic biomarkers including SChLAP1, UCA1 and PCAT14 ( Mehra et al, 2016 ; Fotouhi Ghiam et al, 2017 ; White et al, 2017 ). Further work is exploring lncRNAs as therapeutic targets in PCa using small interfering RNAs (siRNAs), antisense oligonucleotides (ASOs) and small molecule inhibitors ( Fu et al, 2020 ). Therefore, there is significant interest in the role ncRNAs may play in the future management of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have attracted the attention of more and more researchers. 8 , 27 , 28 An increasing number of studies have reported that lncRNAs are dysregulated and are essential regulators and tumor facilitators in cervical cancer. 29 Hence, identifying the lncRNAs involved in cervical cancer and exploring their detailed roles will be beneficial for developing effective targets to guide cancer diagnosis, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA was initially thought to be the noise of gene transcription because it does not have an open reading frame and rarely participates in encoding proteins. However, lncRNAs have been confirmed in recent years for the regulation of various diseases by binding to microRNAs or proteins, thereby participating in the occurrence, progression, and prognosis of diseases (5). The abnormal expression of lncRNA plays an important role in various cancers, such as hepatocellular carcinoma, breast cancer, prostate cancer, and non-small-cell lung cancer (NSCLC) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…However, lncRNAs have been confirmed in recent years for the regulation of various diseases by binding to microRNAs or proteins, thereby participating in the occurrence, progression, and prognosis of diseases ( 5 ). The abnormal expression of lncRNA plays an important role in various cancers, such as hepatocellular carcinoma, breast cancer, prostate cancer, and non-small-cell lung cancer (NSCLC) ( 5 7 ). Therefore, it has been proposed that lncRNAs can become tumor biomarkers.…”
Section: Introductionmentioning
confidence: 99%